Factors Influencing Leadership Behaviour in Dentistry: A Narrative Review - Sara Sherzad Rasool; Azizah Ahmad Fauzi; Mahadir Ahmad; Ahmad Shuhud Irfani Zakaria; Farinawati Yazid (Asian Journal of Medicine & Health Sciences, 2023)
Objective: This paper aims to have an overview of the factors influencing leadership behaviour in dentistry and other contributing factors to leadership in other healthcare systems that also potentially influence leadership behaviour in dentistry. Methodology: Three electronic databases were searched (Web of Science, Scopus and ProQuest). A total of sixteen articles were included in the final review. A combination of the following sets of keywords: 1) leadership AND 2) dentistry OR healthcare AND 3) factor OR influence were searched in the database. Results: The literature review explored about educational approach, as well as the leadership opportunities approach as contributing factors in the development of leadership behaviour in dental society. Other factors that are potentially contribute to leadership behaviour in dentistry also explored by looking at factors that influence leadership in other healthcare systems. Effective education and leadership experience are crucial to exhibiting leadership behaviour in dentistry. Other factors that are proven to have a positive influence on leadership behaviour in other healthcare systems such as self-management skills and communication skills are worth to be further explored in dental society. Conclusion: This literature review recommends further research to correlate the factors that potentially affect leadership behaviour with the effectiveness of leadership behaviour in the dental community. This will provide a better understanding of the necessary skills that need to be incorporated into dental education to promote dental practitioners with effective leadership behaviour.